Connecting Africa and Asia Afrasia as a Benign Community - Mine, Yoichi (New Regionalisms Series, 2022)
By 2100, more than 80 per cent of the world's population is expected to live in Afrasia (Africa and Asia). This book draws lessons from history, provides a new cognitive map of the world, and discusses multiple challenges global citizens will face in the age of Afrasia, an emerging macro-region. The centre of gravity of the world is shifting. Whether the world can manage a soft landing into sustainable equilibrium depends on the nature of the dialogue people in Africa and Asia will organise. The author argues that a state of equilibrium between the two is achievable, provided issues related to gender, employment, agriculture, human-nature relationships, and multicultural coexistence are simultaneously addressed. Can future Afrasia present itself as a community determined not to allow the return of predatory practice internally and externally? Will the fates of African and Asian peoples converge or diverge? How about the future relationships between Afrasia and the rest of the world? Exploring these questions using multiple disciplines, this book will be of interest to professional researchers and graduate students in IR and Afro-Asian relations, as well as Asian and African area studies, demography, geography, history, development economics, anthropology, language education, and religious studies.